MENANAMKAN KECERDASAN EMOSIONAL PADA ANAK USIA DINI MELALUI CERITA DAN MUSIK - Hariyanto Hariyanto (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
Many peoples say, aggressive childrens have a tendency to be naughty even they are justified as bad boys, stubborn, and difficult to mansge. As long as their aggressiveness is positive, it does not matter to them. The environment is quite influential in helping them grow. Emotional Smart is intended to provide the ability for the child to be able to process and train the emotional stability. This is certainly through help and assistance provided by parents and teachers. Among the media that can help the development of children’s emotional intelligence are story and music. Many studies stated that these two things not only help the child in developing intellectual intelligence, but also in developing his emotional intelligence. These two media will be discussed in this article.